Extraction of Lignan from the Leaves of Smallanthus sonchifolius and its Antioxidant Activity - Lv, Jinling; Liao, Zhen; Wang, Lan; Yang, Guangyu; Yang, Yaling (Asian Journal of Chemistry, 2011)
A new lignan, smallanlignan B (1) together with seven known lignans (2-8) were isolated from the leaves of S. sonchifolius. Their structures were elucidated by the analysis of spectroscopic data. The antioxidant activity of smallanlignan B was also evaluated and it showed antioxidant activity with an IC50 value of 2.18 mg/mL.